Mutation rates at the glycophorin A and HPRT loci in uranium miners exposed to radon progeny. Issue 7 (July 1996) - Shanahan, E M; Peterson, D; Roxby, D; Quintana, J; Morely, A A; Woodward, A
Abstract : OBJECTIVES–To find whether a relation exists between estimated levels of exposure to radon and its progeny and mutations in hypoxanthine phosphoribosyl transferase (HPRT) and glycophorin A in a cohort of former uranium miners. METHODS–A cohort study involving a sample of miners from the Radium Hill uranium mine in South Australia, which operated from 1952 to 1961. Radiation exposures underground at Radium Hill were estimated from historical radon gas measures with a job exposure matrix. Workers from the mine who worked exclusively above ground according to mine records were selected as controls. In 1991-2 miners were interviewed and blood taken for measurement of somatic mutations. Mutation rates for HPRT and glycophorin A were estimated with standard assay techniques. RESULTS–Homozygous mutations of glycophorin A were increased in underground miners (P = 0.0027) and the mutation rate tended to rise with increasing exposure with the exception of the highest exposure (> 10 working level months). However, there was no association between place of work and either the hemizygous mutations of glycophorin A or the HPRT mutation. CONCLUSIONS–There may be an association between glycophorin A mutations and previous occupational exposure to ionising radiation. However, not enough is known at present to use these assays as biomarkers for historical exposure in underground mining cohorts.